The impact of sporting event rituals on the wellbeing of Chinese university students - Liu, Qingfeng; Chen, Yu; Liu, Bing (Frontiers in Psychology, 2025)
BackgroundAs China ascends to become the world’s second-largest economy, its position at 68th in the 2024 Global Wellbeing Ranking underscores the persistence of the Easterlin Paradox. University students, who are expected to represent one of the most vibrant and promising social groups, are increasingly affected by mental health issues such as depression, self-harm, and even suicide, indicating that their sense of wellbeing remains insufficient and requires urgent attention. Some scholars argue that happiness is a form of capability that should be cultivated through public education interventions. As the fifth-largest component of China’s wellbeing economy, the sports industry, particularly sports events, which serve as a quintessential form of social ritual, plays a significant role in the pursuit of happiness. Building on this perspective, the present study proposes a theoretical model in which sports event rituals are conceptualized as the independent variable, university students’ wellbeing as the dependent variable, perceived social support as the mediating variable, and physical activity as the moderating variable.MethodsThis study conducted a questionnaire survey among university students in Shanghai, yielding 1,256 valid responses. The data were analyzed using SPSS 26.0 and AMOS 24.0 to examine reliability and validity, as well as to test the hypothesized paths through regression analysis.Results(1) Sporting event rituals have a significant positive effect on university students’ perceived wellbeing; (2) Perceived social support plays a significant mediating role in the relationship between sporting event rituals and students’ wellbeing; (3) Physical activity significantly moderates both pathways: it exerts a negative moderating effect on the relationship between sporting event rituals and wellbeing, and a positive moderating effect on the relationship between perceived social support and wellbeing.ConclusionThe findings contribute to a deeper understanding of the social role of sporting event rituals and provide a useful reference for addressing challenges in university sports education within developing country contexts.